Energy expenditure of agricultural workers in an area of endemic schistosomiasis in the Sudan. Issue 1 (January 1987) - el Karim, M A; Collins, K J; Dore, C
Abstract : Indices of physiological performance in the field under natural working conditions were measured in 46 Sudanese Gezira villagers and related to exercise performance under controlled laboratory conditions. The effect of Schistosoma mansoni infection on energy expenditure in the field was also investigated. A highly significant positive association between the maximal aerobic power output (VO2 max) measured in the laboratory with energy expenditure in the field (r = + 0.51, p less than 0.001) and with changes in body weight during work (r = 0.41, p less than 0.01) was found. The villagers' energy expenditure in field work amounted to 25-28 KJ/min, which corresponded to more than 50% of their predicted VO2 max. They maintained that relative work level for more than an hour. The differences in energy expenditure between moderately infected and non-infected villagers with schistosomiasis did not attain statistical significance but the number of non-infected subjects on which the comparison was based was small.